Recurrence of clinical events at the same anatomical location in patients with MOG antibody-associated disease. (March 2021) - Hyun, Jae-Won; Kwon, Young Nam; Lee, Hye Lim; Jeong, Woo Kyo; Lee, Hye Jung; Kim, Byoung Joon; Kim, Seung Woo; Shin, Ha Young; Shin, Hyun-June; Oh, Sun-Young; Lee, Min Young; Kim, Su-Hyun; et al.
Objectives: Likelihood of clinical events occurring within the same anatomical location in patients with myelin oligodendrocyte glycoprotein antibody-associated disease (MOGAD) was retrospectively investigated. Methods: A total of 236 clinical events in 90 patients with MOGAD from nine referral hospitals were analyzed via logistic regression, and odds ratios (ORs) were calculated. Anatomical lesion location was divided into four groups; optic nerve, spinal cord, cerebral hemisphere, and brainstem/cerebellum. Results: At all locations, there was an increased likelihood of a second attack occurring at the same location as the initial event (cerebral hemisphere OR = 22.14, brainstem/cerebellum OR = 18.4, spinal cord OR = 9.1, and optic nerve OR = 7.8). There was an increased likelihood of a third attack occurring at the same location as the initial event in the optic nerve (OR = 14.9), cerebral hemisphere (OR = 11.7), and spinal cord (OR = 6.7). There were positive trends toward a third clinical event occurring at the same location as the first and/or second events if the event was in the optic nerve (OR = 13.5), cerebral hemisphere (OR = 6.9), or spinal cord (OR = 5.7). Conclusions: The current study suggests that clinical relapses of MOGAD during early stage tend to recur at the same anatomical locations in the central nervous system.